Influence of Hearing Rehabilitation With Active Middle Ear and Bone Conduction Implants on Postural Control - Seiwerth, Ingmar; Brylok, Antonia; Schwesig, René; Rahne, Torsten; Fröhlich, Laura; Lauenroth, Andreas; Hullar, Timothy E.; Plontke, Stefan K. (Frontiers in Neurology, 2022)
Background As audition also seems to contribute to balance control, additionally to visual, proprioceptive and vestibular information, we hypothesize that hearing rehabilitation with active middle ear and bone conduction implants can influence postural control. Methods In a prospective explorative study, the impact of hearing rehabilitation with active middle ear (Vibrant Soundbrige (VSB), MED-EL, Innsbruck, Austria) and bone conduction implants (Bonebridge (BB), MED-EL, Innsbruck, Austria) on postural control in adults was examined in three experiments. Vestibulospinal control was measured by cranio-corpography (CCG), trunk sway velocity (°/s) by the Standard Balance Deficit Test (SBDT), and postural stability with a force plate system, each time in best aided (BA) and unaided (UA) condition with frontal-noise presentation (Fastl noise, 65 dB SPL), followed by subjective evaluation, respectively. Results In 26 subjects (age 55.0 ± 12.8 years; unilateral VSB/BB: n=15; bilateral VSB/BB: n=3, bimodal (VSB/BB + hearing aid): n=8), CCG-analysis showed no difference between BA and UA conditions for the means of distance, angle of displacement, and angle of rotation, respectively. Trunk sway measurements revealed a relevant increase of sway in standing on foam (p=0.01, r = 0.51) and a relevant sway reduction in walking (p=0.026, r = 0.44, roll plane) in BA condition. Selective postural subsystem analysis revealed a relevant increase of the vestibular component in BA condition (p=0.017, r = 0.47). As measured with the Interactive Balance System (IBS), 42% of the subjects improved stability (ST) in BA condition, 31% showed no difference and 27% deteriorated, while no difference was seen in comparison of means. Subjectively, 4-7% of participants felt that noise improved their balance, 73-85% felt no difference and 7-23% reported a deterioration by noise. Furthermore, 46-50% reported a better task performance in BA condition, 35-46% felt no difference and 4-15% found the UA situation more helpful. Conclusions Subjectively, approximately half of participants reported a benefit in task performance in BA condition. Objectively, this could only be shown in one mobile SBDT-task. Subsystem analysis of trunk sway provided insights in multisensory reweighting mechanisms.